How Long is Safe? Setting the Cutoff for Uncomplicated Third Stage Length: A Retrospective Case-Control Study. Issue 1 (March 2017) - Shinar, Shiri; Schwartz, Anat; Maslovitz, Sharon; Many, Ariel
Abstract : ( Birth. 2016;43(1):36–41) Postpartum hemorrhage (PPH) is one of the main risk factors of a prolonged third stage of labor, which is usually 5 to 20 minutes; only 8% of placentae remain undelivered by 20 minutes. The incidence of PPH worldwide is about 6% for >500 mL of blood loss and 1.86% for >1000 mL of blood loss despite active management of the third stage. The objective of this study was to determine the optimal time until undertaking manual placental removal in an uncomplicated third stage while taking into consideration the risk for blood transfusion.